ANALYSIS OF RADIATION THERAPY EQUIPMENT STATUS IN UKRAINE - Lilya Averyanova; Victor Starenkiy (Сучасний стан наукових досліджень та технологій в промисловості, 2020)
The subject matter of the article is review and analysis of existing radiation treatment technologies, availability and efficiency of use of modern radiotherapy equipment in regions Ukraine according to European radiotherapy development trends. The goal of the work is to analyze the current status of radiotherapy equipment in Ukraine and to find the ways for extension of its use. The following tasks were solved in the article: the analysis of distribution of radiotherapy machines in Ukraine, estimation of current number of radiotherapy machines per million people for all regions and needs of radiotherapy centers of Ukraine in high precision conformal treatment machines. The following methods used – documentary data analysis, comparison and summarizing. The following results were obtained – estimated that according to requirements of IAEA that necessary number of megavoltage treatment machines in Ukraine should be near 200. Use of 90 machines covers only 45% needs of Ukrainian population in radiation treatment. According to DIRAC data 61 of 65 Co-60 machines in Ukraine are used during more than 20 years, Co-60 sources in 23 these machines now have Dose rate less than 0.4 Gy/min and must be replaced urgently. Conclusions: The main actual aspects of technical status of equipment for External-beam radiation therapy in Ukraine were discussed. Existing radiotherapy facilities were analyzed from the point of view of real needs and possibilities of Ukrainian radiation oncology. As a conclusion, the results of this analysis demonstrate a significant heterogeneity in the access to modern radiotherapy equipment in different regions of Ukraine. The qualitative analyses of used radiotherapy equipment demonstrate its significant technical backwardness. The results of this analysis may be used as technical recommendations for improvement of radiotherapy facilities in Ukraine.